Detection of recurrent transmission of 17q12 microdeletion by array comparative genomic hybridization in a fetus with prenatally diagnosed hydronephrosis, hydroureter, and multicystic kidney, and variable clinical spectrum in the family - Chih-Ping Chen; Shuenn-Dyh Chang; Tzu-Hao Wang; Liang-Kai Wang; Jeng-Daw Tsai; Yu-Peng Liu; Schu-Rern Chern; Peih-Shan Wu; Jun-Wei Su; Yu-Ting Chen; Wayseen Wang (Elsevier, 2013)
Objective: This study was aimed at detection of recurrent transmission of the 17q12 microdeletion in a fetus with congenital anomalies of the kidney and urinary tract. Materials and Methods: A 35-year-old woman was referred to the hospital at 20 weeks' gestation because of hydronephrosis in the fetus. The mother was normal and healthy. Her second child was a girl who had bilateral dysplastic kidneys that required hemodialysis, and died at the age of 5 years. During this pregnancy, the woman underwent amniocentesis at 18 weeks' gestation because of advanced maternal age. Cytogenetic analysis revealed a karyotype of 46,XY. Prenatal ultrasound showed left hydronephrosis with a tortuous ureter, right hydronephrosis, and increased echogenicity of the kidneys. Fetal magnetic resonance imaging showed right dilated renal calyces, left hydronephrosis, hydroureter, and multicystic kidney. The pregnancy was subsequently terminated. Array comparative genomic hybridization (aCGH) and fluorescence in situ hybridization were applied for genetic analysis using umbilical cord, maternal blood, and cultured amniocytes. Results: aCGH analysis on umbilical cord detected a 1.75-Mb deletion at 17q12 including haploinsufficiency of LHX1 and HNF1B. aCGH analysis on maternal blood detected a 1.54-Mb deletion at 17q12 including haploinsufficiency of LHX1 and HNF1B. Metaphase fluorescence in situ hybridization analysis on cultured amniocytes and maternal blood lymphocytes using 17q12-specific bacterial artificial chromosome probe showed 17q12 microdeletion in the fetus and the mother. Conclusion: Prenatal diagnosis of recurrent renal and urinary tract abnormalities in the fetus should include a differential diagnosis of familial 17q12 microdeletion.